Reduced Evoked Gamma Oscillations in the Frontal Cortex in Schizophrenia Patients: A TMS EEG Study - Ferrarelli, Fabio; Massimini, Marcello; Peterson, Michael J.; Riedner, Brady A.; Lazar, Mariana; Murphy, Michael J.; Huber, Reto; Rosanova, Mario; Alexander, Andrew L.; Kalin, Ned; Tononi, Giulio (The American journal of psychiatry, 2008)
Objective: Transcranial magnetic stimulation (TMS) combined with high-density electroencephalography (EEG) can be used to directly examine the properties of thalamocortical circuits in the brain without engaging an individual in cognitive or motor tasks. The authors investigated EEG responses in schizophrenia patients and healthy comparison subjects following the application of TMS to the premotor cortex. Method: Sixteen schizophrenia patients and 14 healthy comparison subjects were recruited to participate in the study. Participants underwent three to five TMS high-density EEG sessions at various TMS doses. The following three aspects of TMS-evoked responses were analyzed: amplitude, synchronization, and source localization. Results: Relative to healthy comparison subjects, schizophrenia patients had a marked decrease in evoked gamma oscillations that occurred within the first 100 msec after TMS, particularly in a cluster of electrodes located in a fronto-central region. These oscillations were significantly reduced in amplitude (calculated using global-mean field power and event-related spectral perturbation analysis) and synchronization (measured using intertrial coherence). Furthermore, source modeling analysis revealed that the TMS-evoked brain activation underlying these gamma oscillations in patients with schizophrenia did not propagate (as it did in healthy comparison subjects) and was mostly confined to the stimulated brain region. Conclusions: Schizophrenia patients showed a decrease in EEG-evoked responses in the gamma band when TMS was applied to directly stimulate the frontal cortex while these responses were recorded. Since EEG responses to direct cortical stimulation are not affected by an individual's motivation, attention, or cognitive capacity and are not relayed through peripheral afferent pathways, these findings suggest that there might be an intrinsic dysfunction in frontal thalamocortical circuits in individuals with schizophrenia.